1997
DOI: 10.1159/000189558
|View full text |Cite
|
Sign up to set email alerts
|

Antiproteinuric Effect of Ciclosporin A in Adriamycin Nephropathy in Rats

Abstract: Ciclosporin A (CsA) can reduce proteinuria in various forms of human and experimental glomerulopathies. This antiproteinuric effect can be the result of a decrease of immunological damage, a decrease in the glomerular filtration rate (GFR), or a change in the permselective properties of the glomerular capillary wall. In this study we investigated the effect of CsA on Adriamycin-induced nephropathy in rats. A single intravenous injection of Adriamycin (5 mg/kg body weight) induced a severe nephrotic syndrome wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
(20 reference statements)
2
10
0
Order By: Relevance
“…The changes reflect many functional alterations such as a drop in glomerular filtration rate, glomerular capillary damage and tubulotoxicity. These characteristic features of DOX-induced nephropathy are similar to those previously reported by other investigators (Desassis et al 1997;Montilla et al 1997;Venkatesan et al 1997;Zima et al 1997).…”
Section: Discussionsupporting
confidence: 91%
“…The changes reflect many functional alterations such as a drop in glomerular filtration rate, glomerular capillary damage and tubulotoxicity. These characteristic features of DOX-induced nephropathy are similar to those previously reported by other investigators (Desassis et al 1997;Montilla et al 1997;Venkatesan et al 1997;Zima et al 1997).…”
Section: Discussionsupporting
confidence: 91%
“…The role of SRL in the development of proteinuria is completely unknown. First of all, one can speculate that the increase in proteinuria is related to haemodynamic changes and/or changes in glomerular permselectivity after relief of CsA exposure (50). The insidious increase in proteinuria in our patients however, is against this hypothesis.…”
Section: Discussionmentioning
confidence: 58%
“…Time Response Study-In a previous study (36), we compared different doses of ADR. We found that a dose of 5 mg/kg body weight (BW) Adriamycin® (Adriablastina; Farmitalia, Milan, Italy) was optimal to induce proteinuria.…”
Section: Experimental Designmentioning
confidence: 99%